6 ft. 10 in.
7 ft 3 in. You can subtract 2 in from 5 in to get 3 in, then subtract 6 ft from 13 ft to get 7 ft and add the two results to get 7'3".
71
11
-11
Add 11 -6 + 11 = 5
14 feet, 11 inches.
I met him, he is about 5' 11''
11 ft. 11+11+6+6=34
6 ft. 10 in.
The pattern rule for the given sequence is that each number is the sum of the previous number and a specific increment. In this case, the increment appears to be increasing by 1, then 2, then 3, then 4, and finally 5. So, the pattern rule can be expressed as: (n = n-1 + k), where (k) is the increment.
Yes it is possible.
5 ft 11 inches
7 ft 3 in. You can subtract 2 in from 5 in to get 3 in, then subtract 6 ft from 13 ft to get 7 ft and add the two results to get 7'3".
5' 6" + 5' 6" = 5' + 5' + 6" + 6" = 5' + 5' + 1" = 11'.
5 ft 11 then grew to 6 ft 0.5-.75.
71